Characterization of creep crack-tip constraint levels for pressurized pipelines with axial surface cracks. (December 2017) - Xu, Lianyong; Zhang, Xingfu; Zhao, Lei; Han, Yongdian; Jing, Hongyang
Highlights: Constraint levels for pipelines with axial surface cracks were demonstrated by Q *. Constraint value of internal crack was higher than external crack. Constraint level would decrease as crack shape changed from elliptical to circular. SENT specimen better replicated crack-tip constraint condition experienced in pipe. Abstract: Through extensive 3D finite element analyzes, the creep crack-tip constraint levels were characterized using a load-independent creep constraint parameter Q* for pipelines with axial surface cracks of different geometrical sizes, which involved in various crack depths and crack shapes. The Q* distribution along the crack front for axial internal surface cracks and axial external surface cracks exhibited the same distribution tendency. However, the constraint level of internal surface cracks was higher than external surface cracks. In addition, the constraint level was improved as the crack depth became deep; in contrast, the constraint level showed a reduction tendency as the crack shape ratio a/c increased from 0.2 to 1.0. The highest constraint levels for the axial surfaces cracks in pipelines approached to that of single-edge notched tension specimen. Finally, two empirical equations for estimating the constraint level were established as a function of crack depth ratio and crack shape ratio for axial surface cracks in pipelines.